Maqasid as-Syari’ah dan Asuransi Syari’ah - Ahmad Yunadi (JESI (Jurnal Ekonomi Syariah Indonesia), 2020)
The study of Islamic insurance and maqasid sharia in this research writing uses a philosophical approach known as analyzing insurance issues using the maqasid sharia approach. The analysis was carried out by descriptive analytical analysis. The author describes the main theme and then analyzes it from maqasid sharia point of view. Induction analysis patterns are carried out to analyze general data before they are identified and concluded in a general conclusion; namely the philosophy of insurance and maqasid sharia. On the other hand, deduction approach is used when the concept of maqasid sharia which is the conclusion of the nash argument is sought for its relevance to be applied in the insurance.Maqasid Shari'a in human life is seeking or getting maslahah (benefit). There are five aspects that must be protected which are known as al-kuliyyah al-khams; religion, soul, mind, descendants and property. On the field, the protection of maqasid sharia against al-kuliyyah al-khams can be done from two sides; the manifestation side (ijabiyah) and the prevention side (salbiyah). Insurance coverage in accordance with maqasid sharia is hifdzu din (protecting religion), hifdzu nafs (protecting life), hifdzu 'aql (protecting the mind), hifdzu nasl (protecting descendants) and hifdzu mal (protecting property).The results of this study indicate that Islamic insurance and maqasid sharia have the same goal in the stipulation of maqasid sharia or at least participate in realizing the benefits of human life.Keyword; insurance, maqasid, sharia.